Provision of agricultural credit to shall holder farmers in Dangme West District, Ghana - Campbell, Alphonso S. O. (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science in Development Planning and Management